2014
DOI: 10.1021/jm500764v
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Stable Colchicine Binding Site Tubulin Inhibitors as Potential Anticancer Agents

Abstract: To block the metabolically labile sites of novel tubulin inhibitors targeting the colchicine binding site based on SMART, ABI, and PAT templates, we have designed, synthesized, and biologically tested three focused sets of new derivatives with modifications at the carbonyl linker, the para-position in the C ring of SMART template, and modification of A ring of the PAT template. Structure–activity relationships of these compounds led to the identification of new benzimidazole and imidazo[4,5-c]pyridine-fused ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 23 publications
0
55
1
Order By: Relevance
“…Even though excellent antitumor effects were observed with daily administration of 75 mg/kg, an MTD was never reached because of its limited solubility. Multiple colchicine site agents with excellent aqueous solubility, in vivo potency and metabolic stability have been identified (Gangjee et al, 2013;Lu et al, 2014;Zhang et al, 2014) so it is reasonable that newer pyrrole analogs with improved aqueous solubility can be generated. Efforts will also be made to increase the in vivo potency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though excellent antitumor effects were observed with daily administration of 75 mg/kg, an MTD was never reached because of its limited solubility. Multiple colchicine site agents with excellent aqueous solubility, in vivo potency and metabolic stability have been identified (Gangjee et al, 2013;Lu et al, 2014;Zhang et al, 2014) so it is reasonable that newer pyrrole analogs with improved aqueous solubility can be generated. Efforts will also be made to increase the in vivo potency.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts will also be made to increase the in vivo potency. The metabolic liabilities of the trimethoxyphenyl moieties were identified in other colchicine site binding agents (Li et al, 2011) and medicinal chemistry optimization has improved these liabilities while still retaining potent cytotoxic activities (Lu et al, 2014). Identification of analogs with better aqueous solubility and in vivo potency will be a future priority.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we reported that imidazopyridine-oxindole derivatives and conjugates of pyrazoleoxindole exhibit excellent antiproliferative activity by inhibiting the polymerization of tubulin and inducing apoptosis. 13,14 5 Benzimidazoles are important due to their wide range of biological activities such as antitumor, 15,16 anti-angiogenesis 17 and anti vascular activity. 18 Some of the benzimidazole pharmacophores like bisbenzimidazole Hoechst 33258 (4) displayed broad spectrum of 10 antiproliferative activity with DNA minor groove binding and inhibition of topoisomerase ability (Fig 1.).…”
Section: Introductionmentioning
confidence: 99%
“…Although Col is not used clinically to treat cancer due to its toxicity, it does exert anti-proliferative effects through the inhibition of microtubule formation leading to mitotic arrest and cell death by apoptosis. However, it has also been shown to produce anti-vascular effects [8] leading to a greater reduction of blood flow in tumors than in normal tissues and the ability to overcome P-glycoprotein efflux pump mediated multidrug resistance [9], which renders Col a model molecule for the development of a series of novel anticancer drugs with a better toxicological profile [1,[10][11][12][13], many of them currently undergoing clinical studies. Nevertheless, as a downside, it has also been reported that the central administration of cytoskeletal poisons, such as Col, causes oxidative stress in animals leading to cognitive impairment [14], and its therapeutic use has been linked to sporadic Alzheimer's disease in humans [15].…”
Section: Introductionmentioning
confidence: 99%